Young Children's Imitative and Innovative Behaviour on the Floating Object Task. Issue 1 (15th July 2012) - Nielsen, Mark
<x xml:space="preserve">Abstract</x> Past research has shown that children will copy the actions of adults with high fidelity, even actions that are obviously causally irrelevant to the modelled outcome. However, this phenomenon has always been documented in cases where a clear functional outcome has been brought about (e.g. getting a box open to retrieve a toy). Here, we demonstrate how young children will continue to adopt the precise actions shown to them by an adult even if the goal of the actions is not realized during modelling. A group of 4‐year‐old participants were presented with a toy lying at the bottom of a Perspex tube. Despite the availability of a bottle of water, and unlike the responses of a group of adults, few children spontaneously identified the solution of pouring the water into the tube to raise the toy up the tube where it could be reached. The majority did so, however, after seeing an adult demonstrate this approach. Critically, children copied the specific method of the adult, even when this involved the unnecessary steps of pouring from the bottle into a cup before pouring from the cup into the tube. These results highlight the value of overimitation to children growing up in a world filled with objects whose operating mechanisms are often hidden or unclear. Copyright © 2012 John Wiley & Sons, Ltd.